2020
DOI: 10.1021/acsmacrolett.0c00638
|View full text |Cite
|
Sign up to set email alerts
|

Local Orientation of Polystyrene at the Interface with Poly(methyl methacrylate) in Block Copolymer

Abstract: The local conformation of polystyrene (PS) at the phase-separated lamellar interface with poly­(methyl methacrylate) (PMMA) in their diblock copolymer (BCP) was examined by sum-frequency generation spectroscopy in conjunction with a full-atomistic molecular dynamics simulation. While PS phenyl groups of BCP were oriented in the interfacial region, they were random in the bulk. Such an interfacial orientation of phenyl groups was not clear for the corresponding blend of PS and PMMA. The PS backbone of BCP was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Most bulk materials have inversion symmetry, while surfaces/interfaces do not. SFG has been extensively applied to study surfaces and interfaces, including buried solid/liquid interfaces. In this study, for a typical SFG experiment, two input laser beams were used: a frequency-fixed 532 nm visible laser beam and a frequency-tunable infrared laser beam with wavenumber tunability from 1000 to 4300 cm –1 . The visible beam was generated by frequency doubling the 1064 nm (20 ps pulse width) output from an EKSPLA Nd:YAG laser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most bulk materials have inversion symmetry, while surfaces/interfaces do not. SFG has been extensively applied to study surfaces and interfaces, including buried solid/liquid interfaces. In this study, for a typical SFG experiment, two input laser beams were used: a frequency-fixed 532 nm visible laser beam and a frequency-tunable infrared laser beam with wavenumber tunability from 1000 to 4300 cm –1 . The visible beam was generated by frequency doubling the 1064 nm (20 ps pulse width) output from an EKSPLA Nd:YAG laser.…”
Section: Methodsmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy was applied in this research to study various interfaces. SFG is a second-order nonlinear optical spectroscopic method, which provides vibrational spectra of surfaces/interfaces. Details regarding SFG theory, experiment, and data analysis have been reported extensively and will not be repeated. Here, only a brief introduction of the SFG technique and related experiments in this study are presented.…”
Section: Methodsmentioning
confidence: 99%
“…A picosecond SFG system was used for experiments in this study (EKSPLA, Lithuania, model PL2231-20-RS232). SFG vibrational spectroscopy was extensively used to probe the surfaces and interfaces of the materials due to its intrinsic surface sensitivity. SFG theories, setups, and instrumentation will thus not be stated in detail. Briefly, two input beams, a visible beam with a fixed wavelength at 532 nm and a frequency-tunable infrared (IR) beam, were overlapped spatially and temporally on the surfaces of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy has been demonstrated to be a suitable tool to understand the change of molecular structures of surfaces and interfaces. SFG enables precisely measuring the molecular structure/behavior of surfaces/interfaces by its surface/interface-sensitive nature. SFG has been extensively applied to study the surface and interfacial molecular structures of polymers, including various polymer adhesives. , In this study, the atmospheric moisture effect on the surfaces of isocyanate-based primers was probed by SFG, and the molecular behaviors of such surfaces were correlated to the macroscopic properties to investigate the relationship. Different conditions in the experiments were set up in a variation of humidity levels and exposure time to understand the influences of their effects on the primer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Their results are in qualitative agreement with the results of experiments in this system. Tanaka et al 27 investigated the local orientation of PS segments of the PS- b -PMMA chains at the interface by atomistic molecular dynamics simulation. It is found that the PS- b -PMMA chains which are located on the interfacial region, are in-plane oriented.…”
Section: Introductionmentioning
confidence: 99%